Catalytic activities of nanowires - Chua, Hao Zi (2015)
Diabetes is a widely known illness that strikes many with a low chance of full recovery. And most commercial glucose sensors are used to monitor diabetes in patients, and many are enzymatic. As such, this report investigates the possibility of using non-enzymatic glucose sensors for early detection of abnormal blood glucose level, and this is done by analysing the catalytic activity of Zinc Oxide (ZnO) nanowires that would be embedded in the sensor. Aqueous Chemical Growth (ACG), or known as solution phase synthesis, is carried out to fabricate high quality ZnO nanowires from Hexamethylenetetramine, i.e. HMTA (C6H12N4), and Zinc Nitrate Hexahydrate, i.e. [Zn(NO3)2  6H2O]. Scanning Electron Microscope (SEM) and X-Ray Diffractometer (XRD) is then used to analyse the crystal growth and morphology of the nanowires. Cyclic Voltammetry (CV) is lastly used to investigate the rate of glucose oxidation under different parameters. This is reflected by the intensity of the current signal for the glucose oxidation peaks, which is function of the catalytic activity of ZnO nanowires. Results show that by using ZnO nanowires, it is able to detect the variations in blood glucose concentrations, making it possible to detect abnormal blood glucose level early and prevent diabetes. Also, slight variations that are possible in human body do not affect the function of ZnO adversely. A more crystalline form of ZnO nanowires can be obtained with an additional annealing at a temperature of 200oC, allowing them to better serve their functions. In conclusion, these results show great possibility for ZnO nanowires to serve as catalyst in the non-enzymatic glucose sensing. Subsequent work can include investigating the stability of ZnO nanowires in the long run where frequent use of sensor is present or experimenting the possibility of the usage of ZnO nanowires in other applications like food testing or fuel cells.